COST ANALYSIS USING TIME DRIVEN ACTIVITY BASED COSTING FOR PHYSIOTHERAPY CONSULTATION PRICING - Pradita Isti Indranila; Rizka Ramayanti (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
The demand for physiotherapy services in Indonesia continues to grow, yet tariffs that are not based on actual cost structures risk margin distortion and reduced operational efficiency. This study calculates the cost of physiotherapy services and evaluates consultation tariffs at Physiotherapy Clinic ABC using the Time-Driven Activity-Based Costing (TDABC) method. A descriptive quantitative design was employed, utilizing 2024 operational data across three service durations: 30, 45, and 60 minutes. Labor costs, non-time direct costs, and overhead were allocated, and unused capacity was assessed. Results show TDABC-based service costs of IDR 563,079, IDR 711,476, and IDR 859,872, while cost-plus pricing yields recommended tariffs of IDR 732,003, IDR 996,066, and IDR 1,289,808, respectively. Comparison with the clinic’s actual tariffs (IDR 620,000; IDR 930,000; IDR 1,240,000) indicates undercosting for shorter sessions. The highest unused capacity, approximately 66%, was observed at the receptionist level. The study demonstrates that TDABC provides more accurate and detailed cost information than conventional methods. These findings offer a practical basis for tariff adjustments and capacity management to enhance efficiency, sustainability, and resource utilization in physiotherapy services.